Pengolahan Limbah Cair Laundry Menggunakan Membran Selulosa Diasetat Berbasis Selulosa Pulp Kayu Sengon (Paraserianthes falcataria) - Setiawan, Vera Roni; Rosnelly, Cut Meurah; Darmadi, Darmadi (Jurnal Rekayasa Kimia & Lingkungan, 2013)
The improvement of laundry activity brought a negative effect on the environment because laundry wastewater have a high content pollutants such as phosphate, surfactants, mineral, nitrogen, COD and other components, so the treatment is needed before being discharged into terristorial water. Laundry wastewater treatment has been conducted by membrane technology. Preparation of cellulose diacetate membranes with ultrafiltration process had be done by phase inversion using dimethylformamide (DMF) as a solvent. The filtration experiment showed that the highest membrane flux was 77,408 L/m2.h at TMP 3 bar. While the lowest flux at TMP 1 bar was 55.649 L/m2.h. Rejection of membrane ultrafiltration for parameters of COD, phosphate, and surfactant were 67%, 72%, and 63% respectively.Keywords: cellulose diacetate membranes, laundry wastewater, flux, rejection